Dye Sensitized Solar Cell (Dssc) With Areca Extract As A Natural Dye Sensitized - Yuant Tiandho; Purwati Purwati; Marlina Marlina; Mahjur Mahjur; Widodo Budi Kurniawan (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2022)
Dye-sensitized Solar Cell (DSSC) is a solar cell that uses dye as one of its components. DSSC is interesting to develop because it can be fabricated simply with low production costs. This study aims to develop a DSSC that uses dye-sensitized from natural ingredients to be environmentally friendly. We chose betel nut (Areca catechu L.) as a natural dye source because betel nut has a reddish-brown color and is often used as a natural dye. The stages of this research consisted of betel nut extraction, TiO2 deposition, manufacture of a carbon layer on the counter electrode, and DSSC fabrication. Measurement of DSSC performance under solar irradiation with an intensity of 292 W/m2 shows that the fabricated DSSC can produce a voltage of up to 216 mV with a current of 0.03 mA. Variations in the concentration of TiO2 positioned on the ITO substrate indicate that higher concentrations of TiO2 can produce higher DSSC voltages